SWI/SNF complex alterations as a biomarker of immunotherapy efficacy in pancreatic cancer - Gregory P. Botta; Shumei Kato; Hitendra Patel; Paul Fanta; Suzanna Lee; Ryosuke Okamura; Razelle Kurzrock (JCI Insight, 2021)
BACKGROUND Immune checkpoint inhibitors (ICIs) fail to demonstrate efficacy in pancreatic cancer. Recently, genomic biomarkers have been associated with response to ICIs: microsatellite instability high (MSI-H) and tumor mutation burden (TMB) > 10 mutations/Mb. Alterations in Switch/Sucrose Nonfermentable (SWI/SNF) chromatin remodeling genes may predispose to improved outcomes with immunotherapy. The current study examined a possible role for SWI/SNF complex abnormalities in pancreatic cancer responsiveness to ICIs.METHODS A database of 6831 cancer patients that had undergone next-generation sequencing (NGS) was filtered for advanced pancreatic cancer, SWI/SNF alterations, and outcomes depending on immunotherapy treatment.RESULTS Nine patients had metastatic pancreatic adenocarcinoma harboring SWI/SNF chromatin remodeling gene alterations and had received ICIs: 7 had an ARID1A alteration (77%); 2, ARID1B (22%); 3, SMARCA4 (33%); 1, SMARCB1 (11%); and 1, PBRM1 (11%). Three patients possessed more than 1 SWI/SNF complex alteration. Only 3 tumors were microsatellite unstable. Eight of 9 patients (89%) achieved an objective response, including a complete remission, with the 2 longest responses ongoing at 33+ and 36+ months. Median progression-free and overall survival was 9 and 15 months, respectively. Responses occurred even in the presence of microsatellite stability, low TMB, and/or low PD-L1 expression.CONCLUSION A small subset of patients with pancreatic cancer have genomic alterations in SWI/SNF chromatin remodeling components and appear to be responsive to ICIs, suggesting the need for prospective trials.TRIAL REGISTRATION ClinicalTrials.gov, NCT02478931.FUNDING Joan and Irwin Jacobs Fund, NIH P30 CA023100 (RK) and LRP KYGF9753 (GPB), the Gershenson, Duarte, and anonymous patient families (GPB).